Processing Instruction effects on moment-by-moment language processing in Spanish Second Language Acquisition - Robayna, Tiffany (Revista Cedotic, 2023)
Due to a lack of research between the fields of Computer Assisted Language Learning (CALL) and Second Language Acquisition (SLA) (Ortega, 2017; Zeigler et al., 2017; Parmaxi & Zaphiris, 2017), the present study seeks to combine these two fields by looking at Input Processing through the use of Processing Instruction (VanPatten, 2015) when implemented on the computer. With a total of 62 participants, 3rd year Spanish language learners from a high school in Florida performed a Self-Paced Reading (SPR) test after going through structured input. This study will compare the data from a pretest and posttest SPR to see if the information learned on the structured input was able to have an overall effect on the minute-to-minute way learners process input. Results showed that participants from the referential activities group were able to show exhibit a change in their processing. Therefore, when creating SLA activities on the computer incorporating referential type activities will help learners change the way they process the input.